2018
DOI: 10.1186/s12974-017-1047-7
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates collagen-induced inflammatory response through the “gut-brain axis”

Abstract: BackgroundPrevious studies have demonstrated that oral administration of curcumin exhibited an anti-arthritic effect despite its poor bioavailability. The present study aimed to explore whether the gut-brain axis is involved in the therapeutic effect of curcumin.MethodsThe collagen-induced arthritis (CIA) rat model was induced by immunization with an emulsion of collagen II and complete Freund’s adjuvant. Sympathetic and parasympathetic tones were measured by electrocardiographic recordings. Unilateral cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 59 publications
1
23
0
1
Order By: Relevance
“…In fact, anticholinergic agents are used for the treatment of diarrhea, because they slow colonic transit and improve stool consistency and frequency [35]. Increasing evidence indicates that the immune and nervous system maintain extensive interactions [12,57]. Our present results further may suggest that the homeostasis of the immune system may be disrupted via influencing the intestinal functions.…”
Section: Discussionsupporting
confidence: 50%
“…In fact, anticholinergic agents are used for the treatment of diarrhea, because they slow colonic transit and improve stool consistency and frequency [35]. Increasing evidence indicates that the immune and nervous system maintain extensive interactions [12,57]. Our present results further may suggest that the homeostasis of the immune system may be disrupted via influencing the intestinal functions.…”
Section: Discussionsupporting
confidence: 50%
“…Alternatively, perhaps the immune modulatory effects are mediated by action in the gut and do not require absorption of the compound. A recent study demonstrated that curcumin, another compound with poor oral availability but potent effects on the attenuating arthritis, was mediated by increasing neuroexcitability of the vagus nerve [ 60 ]. It is interesting to speculate that frondoside A might also activate a similar gut/brain axis.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Curcumin, a traditional remedy and major curcuminoid found in the spice turmeric, has been used for centuries for treating chronic inflammatory diseases [ 16 , 17 , 18 , 19 ]. Recent studies have demonstrated the decisive role of curcumin in treating autoimmune diseases [ 19 , 20 , 21 , 22 ], including experimental autoimmune arthritis, the animal model of rheumatoid arthritis (RA) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. How curcumin exerts its beneficial effect in experimental arthritis is under investigation [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Curcumin As a Remedy For The Treatment Of Rheumatoid Arthmentioning
confidence: 99%